The efficacy of probiotics in the treatment of irritable bowel syndrome: a systematic review. Issue 3 (17th December 2008) - Moayyedi, P; Ford, A C; Talley, N J; Cremonini, F; Foxx-Orenstein, A E; Brandt, L J; Quigley, E M M
Abstract : Introduction: Probiotics may benefit irritable bowel syndrome (IBS) symptoms, but randomised controlled trials (RCTs) have been conflicting; therefore a systematic review was conducted. Methods: MEDLINE (1966 to May 2008), EMBASE (1988 to May 2008) and the Cochrane Controlled Trials Register (2008) electronic databases were searched, as were abstracts from DDW (Digestive Diseases Week) and UEGW (United European Gastroenterology Week), and authors were contacted for extra information. Only parallel group RCTs with at least 1 week of treatment comparing probiotics with placebo or no treatment in adults with IBS according to any acceptable definition were included. Studies had to provide improvement in abdominal pain or global IBS symptoms as an outcome. Eligibility assessment and data extraction were performed by two independent researchers. Data were synthesised using relative risk (RR) of symptoms not improving for dichotomous data and standardised mean difference (SMD) for continuous data using random effects models. Results: 19 RCTs (18 papers) in 1650 patients with IBS were identified. Trial quality was generally good, with nine reporting adequate methods of randomisation and six a method of concealment of allocation. There were 10 RCTs involving 918 patients providing outcomes as a dichotomous variable. Probiotics were statistically significantly better than placebo (RR of IBS not improving=0.71; 95% CI 0.57 to 0.88) with a number needed to treat (NNT)=4 (95% CI 3 to 12.5). There was significant heterogeneity (χ 2 =28.3, p=0.001, I 2 =68%) and possible funnel plot asymmetry. Fifteen trials assessing 1351 patients reported on improvement in IBS score as a continuous outcome (SMD=−0.34; 95% CI −0.60 to −0.07). There was statistically significant heterogeneity (χ 2 =67.04, p<0.001, I 2 =79%), but this was explained by one outlying trial. Conclusion: Probiotics appear to be efficacious in IBS, but the magnitude of benefit and the most effective species and strain are uncertain.